A qualitative study exploring the benefits of hospital admissions from the perspectives of patients with palliative care needs. (September 2015) - Robinson, Jackie; Gott, Merryn; Gardiner, Clare; Ingleton, Christine
Background: The acute hospital plays a significant role in caring for people with a life-limiting illness. Most research to date has focused exclusively upon the negative aspects of hospitalisation. Currently, there is little known about the benefits of hospital admissions for patients with palliative care needs. Aim: The aim of this study was to explore the benefits of hospital admissions, from the perspectives of patients with palliative care needs. Design: A qualitative study design was adopted. Longitudinal, semi-structured, face-to-face interviews were used to elicit the views of patients admitted to hospital in one large urban acute hospital in New Zealand. Setting/participants: The study sample comprised 14 patients admitted to Auckland City Hospital between July 2013 and March 2014 who met one of the Gold Standard Framework Prognostic Indicators for palliative care need. Results: Through a process of thematic analysis, four themes were identified from the data: being cared for and feeling safe, receiving care to manage at home, relief for family and 'feeling better and/or getting better'. The benefits of being in hospital were reported to extend beyond treatments received. Most participants reported their preference was to come to hospital even if they had been able to access the care they received in hospital at home. Conclusion: This research contributes to a greater understanding of the benefits associated with hospitalisation for patients with palliative care needs. The findings suggest that such benefits extend beyond the treatment patients receive and challenge current assumptions regarding the role of the acute hospital in palliative care.